Thermo-hydraulic and exergetic performance of a cost-effective solar air heater: CFD and experimental study. (January 2022) - Nidhul, Kottayat; Yadav, Ajay Kumar; Anish, S.; Arunachala, U.C.
Abstract: An experimental and computational fluid dynamics (CFD) study is carried out to investigate the impact of secondary flow strengthening the thermo-hydraulic performance of discrete multiple inclined baffles in a flat plate solar air heater (SAH) with semi-cylindrical sidewalls. Initially, for a fixed relative baffle height ( R h = 0.1), the relative baffle pitch ( R p ) for continuous baffles is varied in the range of 0.6–1 to obtain the optimum baffle pitch for 6000 < Re < 14000. The impact of gaps at leading, trailing, and both leading and trailing apices are studied as three different configurations with the optimum R p . A maximum thermo-hydraulic performance of 2.69 is obtained for the gap at the trailing apex. The proposed design has a higher collector efficiency, 55–70%, compared to the ribbed rectangular SAH design exhibiting 30–55%. With lower exergy losses, the present SAH design has higher exergetic efficiency (1.5%–2.2%)than ribbed rectangular SAH (0.9%–1.7%) for the range of Re studied. Further, at low Re, the present SAH design has a higher coefficient of performance, indicating that it is cost-effective than ribbed rectangular SAH designs. Abstract : Experimental and computational study of the cost-effective solar air heater. The impact of secondary flow strength on energy and exergetic efficiency is studied. A maximum overall performance of 2.69 is obtained with gap at the trailing apex. The present design exhibits higher collector and exergetic efficiency.